2018
DOI: 10.1016/j.jcma.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high quality of hepatocyte-like cells from induced pluripotent stem cells with Parp1 but lacking c-Myc

Abstract: In conclusion, we demonstrated that Parp1 promoted reprogramming process to generate the high quality of iPSCs, which could be used as a high quality source of hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…PARP1 was able to facilitate the reprogramming of senescent fibroblasts and the resultant iPSCs were differentiated into hepatocytes. [55][56][57] Combinatorial use of these molecules and transcription factors can synergistically enhance the efficiency of reprogramming and iPSC generation.…”
Section: Small Molecule Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…PARP1 was able to facilitate the reprogramming of senescent fibroblasts and the resultant iPSCs were differentiated into hepatocytes. [55][56][57] Combinatorial use of these molecules and transcription factors can synergistically enhance the efficiency of reprogramming and iPSC generation.…”
Section: Small Molecule Modulatorsmentioning
confidence: 99%
“…Some studies have reported the use of poly (ADP ribose) polymerase 1 (PARP 1) which catalyses ADP ribosylation, as a reprogramming factor replacing c‐Myc. PARP1 was able to facilitate the reprogramming of senescent fibroblasts and the resultant iPSCs were differentiated into hepatocytes 55–57 . Combinatorial use of these molecules and transcription factors can synergistically enhance the efficiency of reprogramming and iPSC generation.…”
Section: Reprogramming Factorsmentioning
confidence: 99%
“…This development is the result of the careful selective expression of transcription factors together. Hepatocyte differentiation is recognized to be coordinately controlled by the act of multiple hepatocyte nuclear transcription factors, for example, hepatocyte nuclear factor (HNF)-1α and -1β; HNF-3α, -β, and -γ; HNF-4α, HNF-6; and CCAAT/enhancer-binding protein α and β [213]. A liverenriched transcription factor, HNF-3β, prompts the primary development of the endoderm, the predecessor to produce the liver.…”
Section: Genetic Manipulation In Dictating Hepatic-like Featuresmentioning
confidence: 99%
“…A liverenriched transcription factor, HNF-3β, prompts the primary development of the endoderm, the predecessor to produce the liver. HNF-3β in the developing endoderm is essential for the expression of HNF-4α, which shows a potential action in hepatocyte differentiation [213,214]. Recently, HNF-3β Overexpression has been presented to prompt endoderm differentiation of ES cells.…”
Section: Genetic Manipulation In Dictating Hepatic-like Featuresmentioning
confidence: 99%
See 1 more Smart Citation